Prevalence study of overweight/obesity in young adults students and associated factors - Garcia, Bianca Maria Schneider Pereira; Menezes, Rosiely Libertino de; Souza, Luara Cauper Antony e; Gama, Wellington Mota; Silva, Danielle Furtado da; Neto, Pedro Vieira da Silva; Costa, Allyson Guimarães da; Marrie, Adriana Malheiro; Gonçalves, Roberta Lins; Sanches, Fernanda Figueroa; Fernandes, Tiótrefis Gomes; Leon, Elisa Brosina de (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Obesity is determined by energy imbalance between consumed calories and spent calories. The projection is that, in 2025, about 2.3 billion adults are overweight and over 700 million obese and this is largely associated with an increase in the prevalence of chronic non-communicable diseases. Objectives: The objective of the study was to identify the biological and social-behavioral factors associated with the prevalence of overweight /obesity in a sample of young university students. Method: The study was approved by the Research Ethics Committee of the Federal University of Amazonas. A cross-sectional study was conducted in which were evaluated 174 participants with a mean age of 21 (± 4.3) years, from Federal University of Amazonas, academics of the Physiotherapy and Physical Education Courses. A self-administered questionnaire, that included personal and behavioral data, anthropometric data and blood pressure measurements, was applied. In addition, blood was collected to analyze the lipid profile, glycemia, glycated hemoglobin and insulin and cytokines. The Poisson regression model was used, considering in the final model those variables with p< 0.05. Results: The study showed that 42% (n=73) of the evaluated individuals were overweight/obese. The variables significantly associated with overweight/obesity after Poisson analysis were elevated diastolic blood pressure, elevated hip circumference, elevated high neck circumference, and alcohol consumption. Conclusion: It was observed in the study that the behavioral and anthropometric determinants were significantly associated with the increase in the prevalence of overweight/obesity in the sample evaluated. It should be noted that alcohol consumption, from one to five times a week, was significantly associated with the prevalence analyzed.